2017
DOI: 10.1371/journal.pone.0188592
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA detection in plasma and cervical samples of women with a recent history of low grade or precancerous cervical dysplasia

Abstract: Circulating HPV DNA has been previously described in women with advanced stages of cervical cancer and has been suggested to be a prognostic marker of disease recurrences and metastases. Only a few studies have reported the presence of HPV DNA in bloodstream of patients with low grade or precancerous cervical lesions. This study aimed to define if HPV DNA could be detected in plasma samples of 120 women referred for a recent history of cervical dysplasia who presented with lesions ranging from High Squamous In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 35 publications
8
41
0
1
Order By: Relevance
“…HPV DNA has also been detected in PBMC of patients with cervical cancer . In addition, HPV DNA was detected in serum or plasma of patients with precancerous cervical dysplasia, head and neck squamous cell carcinoma, and oropharyngeal carcinoma . The presence of HPV DNA in blood from these patients has been explained by the presence of metastatic infected cells or remains of HPV‐infected cells in blood.…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA has also been detected in PBMC of patients with cervical cancer . In addition, HPV DNA was detected in serum or plasma of patients with precancerous cervical dysplasia, head and neck squamous cell carcinoma, and oropharyngeal carcinoma . The presence of HPV DNA in blood from these patients has been explained by the presence of metastatic infected cells or remains of HPV‐infected cells in blood.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that PBMCs bind both virus and viral DNA. Other studies have 419 demonstrated that viral DNA can be detected in serum and plasma (Cocuzza et al, 2017;Jeannot 420 et al, 2016). We have detected viral DNA in serum of the infected mice.…”
Section: Viral Dna Was Detected In Blood Samples Of Crpv Infected Rabmentioning
confidence: 96%
“…These proof‐of‐concept studies could also be applicable to other viral cancers such as HPV‐induced cervical cancer and hepatitis B/C (HBV/HCV)‐induced liver cancer. HPV‐DNA can be detected in plasma, although the smaller studies published so far show conflicting results regarding whether the presence of cell‐free HPV‐DNA can distinguish between infected individuals, those with precancerous lesions and those with cervical carcinoma . Elevated levels of HBV DNA in serum are a strong predictor of risk of hepatocellular carcinoma , but there are few published studies on the association between plasma hepatitis virus DNA and cancer and its role as a biomarker is therefore not yet established.…”
Section: Can Ctdna Be Used In Cancer Screening Programmes In Defined mentioning
confidence: 99%